Southern farmers and their stories : memory and meaning in oral history - Walker, Melissa, 1962- (Lexington, Ky. : University Press of Kentucky, 2006)
Examining oral history narratives of more than five hundred farmers from all the southern states, Melissa Walker explores how farmers recall their agrarian past and the lessons that they draw from that past. These farmers understood that their way of life was passing--indeed many of them would be pushed off the land forever--and so they told stories to preserve a sense that their way of life mattered. Landowners and sharecroppers; native-born farmers and immigrants, African Americans and whites; and men and women narrate the compelling story of how the rural South was modernized in the twentie.
Three southern farmers tell their stories -- Rural Southerners and the community of memory -- Memory and the nature of transformation -- Memory and the meaning of change -- The present shapes stories about the past.
Includes bibliographical references (pages 281-318) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Southern States -- Social life and customs -- 20th century -- Historiography; Farm life -- Southern States -- History -- 20th century -- Historiography; Southern States -- Rural conditions -- Historiography; Farmers -- Southern States -- Interviews; Oral history; Memory -- Social aspects -- Southern States; Interviews -- Southern States; Southern States -- Biography; Interviewing in journalism -- Southern States; Vie à la ferme -- États-Unis (Sud) -- Histoire -- 20e siècle -- Historiographie; Agriculteurs -- États-Unis (Sud) -- Entretiens; Histoire orale; Mémoire -- Aspect social -- États-Unis (Sud); Interviews -- États-Unis (Sud); États-Unis (Sud) -- Mœurs et coutumes -- 20e siècle -- Historiographie; États-Unis (Sud) -- Conditions rurales -- Historiographie; États-Unis (Sud) -- Biographies; Entretiens -- États-Unis (Sud); oral histories (literary genre); HISTORY -- State & Local; HISTORY -- United States -- State & Local -- South (AL, AR, FL, GA, KY, LA, MS, NC, SC, TN, VA, WV); Interviewing in journalism; Farmers; Interviews; Manners and customs -- Historiography; Memory -- Social aspects; Oral history; Rural conditions -- Historiography; Southern States; Mündliche Überlieferung; Landbevölkerung; Soziale Situation; USA -- Südstaaten; 1900-1999; Electronic books; Biographies; History; Interviews